Financial distress experiences and participation in the U.S. stock market - Bing Chen; Frank P. Stafford; Xiaohui Yang (Cogent Economics & Finance)
Few studies have examined how psychological distress stemming from past financial market experiences influences households’ future financial decisions. Our study addresses this gap. Based on estimates from the Panel Study of Income Dynamics (PSID), non-pension or direct stock market participation by families declined steadily, from approximately 30% in 2001 to around 17% by 2013, with no significant recovery during the market’s rise from 2013 to 2015. During both the dot-com recession and the Great Recession, smaller-balance stockholders were more likely to exit, often incurring realized capital losses. In the 2007–2009 period, stockholders with low net worth and income were more likely to experience an increase in short-term psychological distress. We hypothesize that small-scale investors, often compelled to sell during family liquidity crises, developed a negative perception of stock trading. This experience shaped small-scale investors’ memory, creating a form of confirmatory bias that fostered reluctance to re-enter the market. By contrast, wealthier families generally increased their holdings through each recession. Among the affluent who did exit, distress levels were lower and a return to market participation was more common. Using the PSID data, we assess participants’ distress scores and examine the relationship between stock market participation and past adverse experiences.